KUALITAS PERTEMANAN DAN KOHESIVITAS PADA MAHASISWA ANGGOTA KOMUNITAS VIRTUAL DI BIDANG KESEHATAN MENTAL - Mualimah A. Sovia; Farah Farida Tantiani (Universitas Gunadarma, 2023)
Technological development have created a virtual-based community that allows community members to not always interact directly. This can affect the quality of friendship and group cohesiveness because there is no physical closeness between members. Group cohesiveness is needed so that members remain in the community they follow and achieve community goals. One of the things related to being able to affect group cohesiveness is the friendship between its members. Therefore, this study aims to determine whether there is a relationship between the quality of friendship and cohesiveness in students in virtual communities in the field of mental health. This research uses quantitative methods with correlational research types. Respondents in this study were students who were active in the virtual community X with a total of 106 members. The instrument in this study consisted of a Friendship Quality (FQUA) and Group Environment Questionnaire (GEQ) scale. The data analysis technique in this study used the Pearson product moment correlation test. The results showed that there was a significant relationship between the quality of friendship and cohesiveness among students in virtual community X.